Migration and inter-industry mobility of UK graduates: Effect on earnings and career satisfaction - Maria Abreu; Alessandra Faggian; Philip McCann (European Regional Science Association (ERSA), 2011)
Career progression is often associated with migration and/or industry change, but the relationship between the two, and their effect on the earnings and career satisfaction of recent graduates are not well understood. We analyse the relationship between migration and inter-industry mobility using longitudinal microdata on 5,000 recent UK graduates who finished their studies in 2002/03, and who were surveyed 6 months and 3 Â years after graduation. We define migration as a move of more than 15 km from the location of employment, and analyse the effects of a locational move in conjuction, or in the absence of, a change in industry. We allow for the possibility of selection bias, whereby unobservable characteristics may lead graduates to both change their location and/or industry, and earn a higher or lower salary, by estimating a treatment effects model with multinomial choice. Our results indicate that the effect on both earnings and career satisfaction of a change in location is positive, and there is a strong negative effect associated with changing both location and industry. The results also show that the subject of study is an important determinant of both migration choice and career outcomes for UK graduates.
Keywords: 330